Modifikasi Mesin Las Gesek Cakram - Fendi Eka Setiawan; Nafsan Upara (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2021)
The purpose of this research is to improve the performance of the disc friction welding machine that has been built and is operated, but there is a drawback, namely that there is no measuring device for process parameters such as rotational speed and forging load. In addition, during operation there is a vibration of 1.5 mm / s to 4.9 mm / s which is unacceptable according to ISO-2372 standards, so that these deficiencies can affect the quality of weld production. Repair or modification of this the friction welding machine is carried out by selecting and installing a rotating speed sensor (RPM) and load cell forging loads and installing rubber to dampen vibrations. Furthermore, the function test was carried out with the load, it was obtained that the rotational speed read on the LCD was 3.7% greater than the tachometer and the vibration decreased up to a value of 0.9 mm/s where this value was acceptable according to ISO-2372, while the performance test resulted in welding production for 3 workpieces with plate sheet material AA-110, ASTM A36 and CU-DHP copper with the same thickness, namely 1mm. From the results of the specimen tensile test of the three materials, it was found that the breakdown location was in the welding area where the tensile test value was around 1.2 to 5.1% of the tensile value of the workpiece material.